Change in pH of Oozed fluid in Periodontal Pocket with Repeated Measurements - KOBAYASHI, Ken'ich; SOEDA, Wataru; NAGAO, Masanori; WATANABE, Tatsutomi (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1994)
oozed fluid in periodontal pocket are influenced by the condition of the surrounding tissues. It might be considered that the surrounding tissues would ooze fluid in reaction to the mechanical stimulation. However, no investigation concerning this reaction has been reported. The aim of this study was to clarify the reaction of surrounded tissues by performing repeated measurements of the gingival fluid pH. The values of pH in periodontal pockets of the upper premolars were measured repeatedly. Participants in this study were 10 persons. The values of pH were measured with METOXY. The sensor was made by D. C. reactive sputtering of iridium oxide on the solid substrates, and was 0.5mm in diameter, and 10mm in length. The time needed for measurement was about 5 second with this sensor. The following result were obtained: The pH value changed between the second-third measurement in nine subjects. Eight persons inclined to the alkaline side, one to the acid side and one showed no change. This result indicated that tissues surrounding periodontal pocket reacts against stimulation caused by measurements and oozed reactive fluid. As the sensor in this study was small and the measurement time was short, the mechanical stimulation caused by measurements could be considered less than previous reports. In spite of this, it is meaningful that the tissue surrounding the gingival pocket showed a reaction against this small stimulation. Our result indicates that special care is needed in studying periodontal pocket fluid, and the repeated measurements are not recommended.